Gamma-ray back emission from nanowire array irradiated by ultra-intense relativistic laser pulse - F. T. T. Houng; S. Y. Hoh; I. Yusuff; K. A. Tanaka; J. F. Ong (AIP Advances)
A highly energetic photon is emitted via nonlinear inverse Compton scattering after an electron undergoes scattering with an ultra-intense relativistic laser pulse. In the laser-nanostructured interaction, gamma photons are emitted in different directions due to different electron heating mechanisms. However, the physics that leads to such gamma-photon emission directionality still requires further understanding. This paper shows that ∼53% of the photons emitted from the nanowires fall into the forward-directed cone, with ∼21% of the backward-emitted photons. Using the two-dimensional particle-in-cell simulations, we found that the backward-emitted photons are mainly ascribed to the j × B heating and reflux electrons. The direction of photon emission from the nanowire tip is in the direction of the ponderomotive force. Furthermore, we also demonstrate that the nanowire target attached to the supporting substrate helps to enhance forward photon emission and reduce emission from reflux electrons. Understanding the correlation between the laser heating mechanisms and the directionality of photon emission could provide insights into the generation of collimated gamma rays using nanowire targets for various applications.